2008
DOI: 10.1097/dmp.0b013e318164f440
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Cities Readiness Initiative: Lessons Learned From Boston

Abstract: The federally funded Cities Readiness Initiative (CRI) requires seamless federal, state, and local public health coordination to provide antibiotics to an entire city population within 48 hours of an aerosolized release of anthrax. We document practical lessons learned from the development and implementation of the Boston CRI plan. Key themes center on heightened emphasis on security, a new mass protection model of dispensing, neighborhood-centric clinic site selection, online training of Medical Reserve Corps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…10,11 Specifically, CRI grantees, which now comprise the 72 largest cities in the United States, must demonstrate the ability to dispense countermeasures to all designated at-risk populations within 48 hours of the decision to do so. Although the CRI addresses urban centers, this 48-hour performance goal has assumed near-universal currency in countermeasure dispensing strategies across the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Specifically, CRI grantees, which now comprise the 72 largest cities in the United States, must demonstrate the ability to dispense countermeasures to all designated at-risk populations within 48 hours of the decision to do so. Although the CRI addresses urban centers, this 48-hour performance goal has assumed near-universal currency in countermeasure dispensing strategies across the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Massachusetts, for example, recently described how its statewide public health response infrastructure was essentially completely reinvented since 2004 to meet the CRI requirement. 11 However, no published reports have quantitatively evaluated how outcomes vary in relation to meeting or missing the 48-hour goal; in fact, one recently published model assumed that the first 48 hours of an anthrax response dispensing campaign would constitute just the ''ramp-up'' time to full dispensing capacity, with the actual mass prophylaxis campaign taking over 11 days. 12 The model presented here, first developed in 2002-2003 for the Agency for Healthcare Research and Quality (AHRQ), was used during the initial formulation of the CRI to provide quantitative assessments of the effect of mass prophylaxis interventions on expected hospital surge arrivals in the aftermath of an aerosol anthrax attack (Dr. William Raub, DHHS, personal communication, September 10, 2008.).…”
Section: Introductionmentioning
confidence: 99%
“…Koh et al (2008), in their article "Implementing the Cities Readiness Initiative: Lessons Learned from Boston," pointed out the "Herculean task" of providing prophylactic antibiotics for an entire city population within 48 hr of release of aerosolized anthrax. Koh et al stressed that making point of dispensing (POD) sites operational requires thousands of trained volunteers in a "seamless coordination of federal, state, and local officials" (p. 47).…”
Section: Population-specific Program Planmentioning
confidence: 98%
“…In the event of biological warfare such as anthrax, mass protection of the public must be facilitated within 48 hr of exposure (Koh et al, 2008). Koh et al (2008), in their article "Implementing the Cities Readiness Initiative: Lessons Learned from Boston," pointed out the "Herculean task" of providing prophylactic antibiotics for an entire city population within 48 hr of release of aerosolized anthrax.…”
Section: Population-specific Program Planmentioning
confidence: 99%
“…18 It found that mail carriers served more people per hour per provider than could be reached by operating a fixed dispensing site.…”
Section: Exhibitmentioning
confidence: 99%